The Migration of Australians to Bali, Indonesia: More than Retirees and Surfers - Davies, Amanda; Hoath, A. (Wiley-Blackwell Publishing Asia, 2016)
The factors underpinning the migration of Australian residents to Bali, Indonesia, and the demographic characteristics of the Australian expatriate population in Bali are examined. It is argued that in undertaking a move to Bali, Australian expatriates are employing a deliberate strategy to utilise their existing financial resources and social networks to gain a lifestyle they perceive would not be available to them if they were to remain in Australia. However, it is also argued that there is considerable diversity in the factors underpinning migration decisions. Through a survey of 236 Australians living in Bali, it was found that a complex of place-based and non-place-based factors influenced migration decisions. It was also found that some factors underpinning migration were broadly associated with phase in the life course. While the survey identified only a minor overrepresentation of Australian retirees living in Bali, given the factors that were identified as underpinning migration to Bali, and with the large baby boomer population nearing retirement, it is probable that as Australia's population ages, there will be further growth in the number and proportional share of older Australians living in Bali.